Towards City Resilience: The Influence of Socio-cultural and Economic Features of Housing on Population Growth in Public Residential Estates - Enobong Equere; Eziyi Ibem; Oluwole Alagbe (Journal of Regional and City Planning, 2020)
Although there is increasing knowledge about the role housing plays in promoting resilience in cities, studies on the socio-cultural and economic features of housing that enhance the capacity of public housing schemes to absorb the impacts of rapid population growth in cities of developing countries are limited. This article, therefore, explored the features of selected public residential estates in Abuja, Nigeria with the aim of revealing the socio-cultural and economic features of housing responsible for attracting and sustaining increasing numbers of residents in public housing environments. A questionnaire survey was conducted among 345 residents in seven selected public housing schemes in the study area. In total, 13 variables were investigated and the data were analyzed using categorical regression analysis at 95% confidence level (i.e. p â‰¤ 0.05). With R2 = 0.716, the regression model revealed that the availability of economic activities, mixture of ethnic groups and quality of services made the most significant contributions to explaining the increasing number of residents in the public housing estates sampled. The findings are vital to inform housing designers and developers about the need to give adequate consideration to these features of housing in order to improve the capacity of such schemes to absorb the impacts of rapid population growth and thus contribute to enhancing city resilience in the face of growing negative impacts of rapid urbanization in developing countries. Abstrak. Meskipun ada peningkatan pengetahuan tentang peran perumahan dalam mempromosikan ketangguhan kota-kota, studi tentang dimensi sosial-budaya dan ekonomi perumahan yang meningkatkan kapasitas skema perumahan rakyat untuk menyerap dampak dari pertumbuhan penduduk yang cepat di kota-kota di negara-negara berkembang masih terbatas. Oleh sebab itu, artikel ini mengeksplorasi fitur perumahan rakyat terpilih di Abuja, Nigeria dengan tujuan untuk mengungkapkan fitur sosial-budaya dan ekonomi perumahan yang bertugas untuk menarik dan mempertahankan peningkatan jumlah penduduk di lingkungan perumahan rakyat. Studi ini didasarkan pada survei kuesioner terhadap 345 penduduk di tujuh skema perumahan rakyat terpilih di wilayah studi. Secara keseluruhan, 13 variabel diselidiki dan data dianalisis menggunakan analisis Regresi Kategorikal pada tingkat kepercayaan 95% (P â‰¤ 0,05). Dengan R2 = 0,716, model regresi mengungkapkan bahwa ketersediaan kegiatan ekonomi, campuran kelompok etnis dan kualitas layanan memberikan kontribusi paling signifikan dalam menjelaskan peningkatan jumlah penduduk di perumahan-perumahan yang dijadikan sampel. Temuan ini sangat penting dalam memberi informasi kepada perancang dan pengembang perumahan tentang perlunya memberikan pertimbangan yang memadai terhadap fitur-fitur perumahan ini untuk meningkatkan kapasitas skema tersebut dalam menyerap dampak pertumbuhan penduduk yang pesat, dan, dengan demikian, berkontribusi untuk meningkatkan ketangguhan kota dalam menghadapi dampak negatif yang berkembang dari urbanisasi yang cepat di negara-negara berkembang.Kata kunci. Perumahan, pertumbuhan penduduk, perumahan rakyat, urbanisasi, kota tangguh.